1992
DOI: 10.1111/j.1365-2222.1992.tb02814.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of major inhalant allergens from soybean hulls

Abstract: Proteins responsible for respiratory allergy to soybean have been purified from an extract of soybean hulls. The purification procedure combined size exclusion and reverse-phase HPLC. Two pure glycoproteins (S1 and S2) exhibiting IgE-binding ability, as demonstrated by immunoblotting and ELISA techniques, were obtained. Both proteins displayed low molecular weight values on SDS-PAGE (S1, 7.0 kD; S2 7.5 kD). Protein S1 showed charge microheterogeneity, rendering two bands at pH 6.1-6.2 on IEF, whereas S2 showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 16 publications
0
53
0
1
Order By: Relevance
“…One group includes works on soybean as an inhalant allergen (Bush et a/, 1988;Rodorigo et al, 1990;Gonzalez et al, 1992) and the other group study it as a dietary allergen (Sampson & McCaskill 1985;Herian et al, 1990;Ogawa et al, 1991). For people other than particular instances of workers at soybean mills and inhabitants around harbors unloading soybeans, dietary allergies induced by soybean may be more serious.…”
mentioning
confidence: 99%
“…One group includes works on soybean as an inhalant allergen (Bush et a/, 1988;Rodorigo et al, 1990;Gonzalez et al, 1992) and the other group study it as a dietary allergen (Sampson & McCaskill 1985;Herian et al, 1990;Ogawa et al, 1991). For people other than particular instances of workers at soybean mills and inhabitants around harbors unloading soybeans, dietary allergies induced by soybean may be more serious.…”
mentioning
confidence: 99%
“…González et al [3]identified an allergen from stored soybean hull, Gly m 1, responsible for the asthma outbreaks that took place in Cartagena, Spain. It contains two isoallergens, Gly m 1A and Gly m 1B, with MWs of 7.5 and 7kD, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these proteinic aeroallergens were identified [1, 2]and three of them, Gly m 1A, Gly m 1B and Gly m 2, were purified and their N–terminal amino acid sequence reported [3, 4, 5]. Specific IgE and IgG4 to these three allergens was demonstrated in the sera of soybean asthmatic (SA) subjects [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Among these are Gly m 1a, 1b, Gly m Bd 28k, 30k, Kunitz trypsin inhibitor, 7s globulin, the α and α' subunits of beta conglycinin and others. These proteins induce allergic reactions using molecular weight of IgEbinding soy protein (Beardslee et al 2000;Gonzalez et al 1992;Helm et al 2000;Metcalfe et al 1996;Ogawa et al 2000;Ogawa et al 1991;Rihs et al 1999;Rodrigo et al 1990;Xiang et al 2008). Symptoms of these allergic reactions usually include fever, vomiting, diarrhea, respiratory problems, gastrointestinal upset and anaphylaxis, which is the most severe allergic reaction and can even cause death (Sampson 2000;Taylor and Kabourek 2003).…”
Section: Introductionmentioning
confidence: 99%